ChemInform Abstract: Beyond the Halogen Bond: Examining the Limits of Extended Polybromide Networks Through Quantum‐Chemical Investigations. Issue 21 (6th May 2016) - Easton, Max E.; Chan, Bun; Masters, Anthony F.; Radom, Leo; Maschmeyer, Thomas
Abstract: Reaction energies at 0 K for the association of Br ‐ + 0.5(n‐1)Br2 → [Brn ] ‐ are determined by DFT calculations on the BMK‐D3BJ/6‐311 + G(3df, 2p)//B3‐LYP/def2‐SVP level.